Cover Image. (6th April 2020) - He, Wencai; Livingston, Jordan C.; Sobiesk, Evan R.; Zhou, Jiange; Zhu, Xianchun; Duan, Yuanyuan; Yang, Shan
Abstract : The cover image is based on the Research Article A pilot study on high wavenumber Raman analysis of human dental tissues by Wencai He et al., https://doi.org/10.1002/jrs.5812 .